Artificial neural networks in real-life applications Juan R. Rabuñal and Julián Dorrado, editors - Rabunal, Juan Ramon 1973-; Dorrado, Julian 1970- editor (Idea Group Publishing, 2006)
"This book offers an outlook of the most recent works at the field of the Artificial Neural Networks (ANN), including theoretical developments and applications of systems using intelligent characteristics for adaptability"--Provided by publisher